Accumulation pattern of endogenous cytokinins and phenolics in different organs of 1-year-old cytokinin pre-incubated plants: implications for conservation - Aremu, A O; Plačková, L; Gruz, J; Bíba, O; Šubrtová, M; Novák, O; Doležal, K; Van Staden, J (Plant biology (Stuttgart, Germany), 2015)
A better understanding of phytohormone physiology can provide an essential basis to coherently achieve a conservation drive/strategy for valuable plant species. We evaluated the distribution pattern of cytokinins (CKs) and phenolic compounds in different organs of 1-year-old greenhouse-grown Tulbaghia simmleri pre-treated (during micropropagation) with three aromatic CKs (benzyladenine = BA, meta-topolin = mT, meta-topolin riboside = mTR). The test species is highly valuable due to its medicinal and ornamental uses. Based on UHPLC-MS/MS quantification, mT and mTR pre-treated plants had the highest total CK, mostly resulting from the isoprenoid CK-type, which occurred at highest concentrations in the roots. Although occurring in much lower concentrations when compared to isoprenoid CKs, aromatic CKs were several-fold more abundant in the root of mT pre-treated plants than with other treatments. Possibly related to the enhanced aromatic CKs, free bases and ribonucleotides, plants pre-treated with mT generally displayed better morphology than the other treatments. A total of 12 bioactive phenolic compounds, including four hydroxybenzoic acids, five hydroxycinnamic acids and three flavonoids at varying concentrations, were quantified in T. simmleri. The occurrence, distribution and levels of these phenolic compounds were strongly influenced by the CK pre-treatments, thereby confirming the importance of CKs in phenolic biosynthesis pathways.
Keywords: flavonoidy; Flavonoids; Liliaceae; kořeny rostlin; Hydroxybenzoates; meta-topolins; Acclimatisation; conservation; fenoly; UHPLC; phytochemicals; Plant Roots; regulátory růstu rostlin; Phenols; Coumaric Acids; liliovité; Cytokinins; hydroxybenzoáty; cytokininy; plant growth regulators; Plant Growth Regulators; wild garlic; kyseliny kumarové